2017
DOI: 10.7150/jca.18435
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Metastatic Effect of Semi-Purified Nuphar Lutea Leaf Extracts

Abstract: Nuphar lutea L. SM., leaf and rhizome extracts (NUP), contain nupharidines as active components. Nupharidines belong to the sesquiterpene lactones class of a naturally occurring plant terpenoids. This family of compounds has gained considerable interest for treating infection, inflammation and cancer.NF-κB is a central, downstream regulator of inflammation, cell proliferation and apoptosis. In our previous work we demonstrated strong inhibition of NF-κB activity and induction of apoptosis by NUP. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Based on previous cytotoxic data on cell lines (El‐On et al., ; Ozer et al., , ) and validation on neutrophils (Figure a), two non‐toxic concentrations of Nupharidine (12.5 and 25 μg/ml), were tested on neutrophils. Viability analysis demonstrated approximately 6% non‐vital cells (negative for both apoptosis and necrosis markers) in the control, and 6.41% and 8.39% non‐vital cells in the 12.5 and 25 μg Nupharidine treated cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous cytotoxic data on cell lines (El‐On et al., ; Ozer et al., , ) and validation on neutrophils (Figure a), two non‐toxic concentrations of Nupharidine (12.5 and 25 μg/ml), were tested on neutrophils. Viability analysis demonstrated approximately 6% non‐vital cells (negative for both apoptosis and necrosis markers) in the control, and 6.41% and 8.39% non‐vital cells in the 12.5 and 25 μg Nupharidine treated cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several plant organs of Nuphar lutea (Yellow Water Lilly) are used in traditional medicine for the treatment of arthritis, fever, aches, pains and inflammation (Ozer et al., ). We showed that semi‐purified extracts of Nuphar lutea containing active thio‐sesquiterpene molecules, Nupharidine (6,6′‐Dihydroxythiobinupharidine), have anti‐cancer and pro‐apoptotic activity (Ozer, Fishman, Eilam, Golan‐Goldhirsh, & Gopas, ; Ozer et al., ), as well as anti‐inflammatory (Ozer, Levi, Golan‐Goldhirsh, & Gopas, ) and modulatory effects on NF‐κB (Ozer et al., ). In addition, it has anti‐leishmanial activity (El‐On, Ozer, Gopas, Sneir, & Golan‐Goldhirsh, ) and increased iNOS production by macrophages, against Leishmania major (Ozer, El‐On, Golan‐Goldhirsh, & Gopas, ).…”
Section: Introductionmentioning
confidence: 99%
“…The extract has anti-metastatic properties, synergistically with conventional chemotherapy drugs, both in vitro and in vivo. It also induces phospho-extracellular signal-regulated kinases (ERK) expression [14].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of early studies revealed that the full therapeutic potential of Nuphar products is still largely unexplored by modern research [5]. Nevertheless, recent reports from various laboratories, including ours, on the medicinal properties of Nuphar extracts have indicated potential applications: as anti-inflammatory [6], anti-bacterial [7,8] against pathogenic fungi [9], against the leishmania and trypanosome parasites, [10][11][12], and against cancer [7,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that NUP induced ERK activation. Furthermore, ERK inhibition prevented NF-κB inactivation by NUP [ 5 , 11 , 12 ]. We have recently published that 6,6′-dihydroxythiobinupharidine (DTBN), purified from NUP, very efficiently and covalently inhibited human type II topoisomerase [ 13 ].…”
Section: Introductionmentioning
confidence: 99%